2015
DOI: 10.1007/s10776-015-0288-6
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of LTE-U on Wi-Fi Performance

Abstract: With the exponential growth in mobile data traffic taking place currently and projected into the future, mobile operators need cost effective ways to manage the load of their networks. Traditionally, this has been achieved by offloading mobile traffic onto Wi-Fi networks due to their low cost and ubiquitous deployment. Recently, LTE operating in the unlicensed spectrum has drawn significant interests from mobile operators due to the availability of the unlicensed spectrum. However, the deployment of LTE networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 6 publications
0
64
0
Order By: Relevance
“…Wi-Fi/LTE [119]- [136] Wi-Fi: CSMA/CA; LTE: none -distributed [125], [129] Wi-Fi: CSMA/CA; both: channel allocation (random [125], [129]; graph coloring [125]; avoid occupied channels [129]) -distributed [125], [129]; coordinated [125] [137], [138] both: spectrum splitting between technologies (subcarrier granularity [138]) -likely cooperative [137]; cooperative [138] [139] Wi-Fi: CSMA/CA; LTE: power control in the uplink -distributed [140] Wi-Fi: modified CSMA/CA both: decoding colocated LTE and Wi-Fi receivers [141] Wi-Fi: CSMA/CA LTE: beamforming distributed; LTE nodes also have 802.11 receivers…”
Section: B Coexistence Among Broadband Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wi-Fi/LTE [119]- [136] Wi-Fi: CSMA/CA; LTE: none -distributed [125], [129] Wi-Fi: CSMA/CA; both: channel allocation (random [125], [129]; graph coloring [125]; avoid occupied channels [129]) -distributed [125], [129]; coordinated [125] [137], [138] both: spectrum splitting between technologies (subcarrier granularity [138]) -likely cooperative [137]; cooperative [138] [139] Wi-Fi: CSMA/CA; LTE: power control in the uplink -distributed [140] Wi-Fi: modified CSMA/CA both: decoding colocated LTE and Wi-Fi receivers [141] Wi-Fi: CSMA/CA LTE: beamforming distributed; LTE nodes also have 802.11 receivers…”
Section: B Coexistence Among Broadband Technologiesmentioning
confidence: 99%
“…Wi-Fi/LTE [119]- [141] Impact of coexistence with unmodified LTE on Wi-Fi −no baseline [119], [126], [134]; −vs. standalone [120]- [125], [127]- [131], [135];…”
Section: -30 Stations Of Each Technologymentioning
confidence: 99%
“…11.11.230.018. 1 The "carrier sensing" is done during the CSAT OFF periods to determine channel occupancy by competing technologies and adapt LTE's duty cycle parameters accordingly. be problematic, because it has been demonstrated that the sensing capabilities of the two technologies can be asymmetric and in some cases LTE stations are not able to sense Wi-Fi transmissions [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike WiFi, the LTE does not have shared access mechanisms, since the LTE is designed to operate in a dedicated, licensed band. In [9,10] simulation and theoretical results on the co-existence of LTE and WiFi networks can be found, respectively. It is shown that some sort of coordination between these two networks is necessary.…”
Section: Introductionmentioning
confidence: 99%